MARRIAGE, IN‐LAWS, AND CRIME: THE CASE OF DELINQUENT BROTHERS‐IN‐LAW*. Issue 2 (19th April 2017) - ANDERSEN, LARS HØJSGAARD
Abstract : With marriage comes in‐laws, and if the in‐laws include delinquent males, their delinquency could affect the prosocial effects of the given marriage. In this article, I focus on the effect of having a convicted brother‐in‐law as a general indicator of this broader phenomenon of family‐formation processes impairing the positive impact of marriage on crime desistance. I use registry data on all men from birth cohorts 1965–1975 in Denmark (N = 69, 066) to show that when a man marries, his new family ties to delinquent brother(s)‐in‐law do indeed hinder his criminal desistance. The results that take into account the characteristics of husbands, wives, their shared family‐formation process, and the criminality of male family members suggest that 1) family dynamics tend to keep criminality within family networks and 2) influences from one's broader social network through marriage are important for the protective effects of marriage. Analyses of previous conviction, co‐offending between a man and his brother‐in‐law, as well as analyses of in‐laws who reside in close proximity confirm the two mentioned main findings. In all, the findings reported in this article add to our understanding of the processes by which families are tied, and how these family‐formation processes influence men's behavior.